Karakteristik Fisik Bakso Daging Sapi dengan Penambahan Tepung Kedelai sebagai Pengganti Tepung Tapioka - Riyan Subarkah; Oki Imanudin; Rachmat Somanjaya (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
The purpose of this study was to analyze the dosage of using soy flour on the physical characteristics of beef meatballs and to obtain the results of using soy flour which affected the physical characteristics of beef meatballs. This study used a completely randomized design (CRD) with 5 treatments and 4 replications. The comparison of tapioca flour with soybean flour for each treatment were P0 (100%: 0%), P1 (75% : 25%), P2 (50% : 50%), P3 (25% : 75%), and P4 ( 0% : 100%). The data obtained were analyzed using analysis of variance (ANOVA) and if the results of the ANOVA test show a significant difference, continue with Duncan's further test. The results showed that the addition of soy flour to beef meatballs had a significant effect (P<0,05) on cooking loss, pH, elasticity, and water-holding capacity. The addition of soy flour caused the cooking shrinkage value from P0 to P4 to decrease with an average value of 16.77 to 11.59%, the pH value of meatballs added with soy flour decreased from P0 to P4 with an average value of 6.48 to 6.15%, the elasticity value of meatballs decreased from P0 to P4 with an average value of 73.40 to 30.22% and the water holding capacity of meatballs from P0 to P4 decreased with an average value of 0.74 to 0.63%. This study can be concluded that the addition of soybean meal can produce better physical properties of beef meatballs.